Assessment of water quality of Sungai Galing, Kuantan Pahang - Nuraishah, Abu (2014)
The study of water quality at Galing River, Kuantan was conducted to determine the water quality status of the Galing River based on NWQS standard introduced by the Department of Environment (DOE) and Water Quality Index (WQI). In this study, five stations were selected for sampling and the standard methods were used for analysis. For sampling method, the water samples were taken twice a month starting on September until November. A total of eleven water quality parameters were assessed to obtain the quality at Galing River, which included physical, chemical and biological parameters. These parameters were pH, dissolved oxygen, temperature, turbidity, total suspended solids (TSS), biochemical oxygen demand (BOD), chemical oxygen demand (COD), ammonia nitrogen, heavy metals test, total coliform and Escherichia coli. Based on results it is found that Galing River was classified under class IV according to the WQJ, which the river water is suitable for irrigation only. The study revealed that sample station located in the commercial area showed the highest level of river pollution. River pollution was driven by the high content of contaminants and it was reduced the oxygen content in the water. Through the testing of heavy metals found that there was a high concentration of ferum and cadmium and it may affect the human health and environment. Precautions should be taken immediately by the authorities to control water pollution at Galing River and it should be supported by all parties.